Presumptive Jamestown Canyon viral retinitis - Muqit, M M K; Devonport, H; Smith, R A; Dhillon, B (British journal of ophthalmology, 2008)
Serological testing for CMV, herpes simplex virus (HSV), varicella zoster virus (VZV) and active syphilis infection was normal. Full blood count, renal function, ESR, C-reactive protein, ACE levels, antinuclear antibody and chest x ray were all normal.